Estimates of State Domestic Product of Haryana (Revised Series) 1970-71 To 1980-81 - Planning Commission (Planning Commission, 1983)
This brochure provides revised series of Estimates of State Domestic Product from 1970-71 to 1980-81 both at current and constant (1970-71) prices. The revision has been necessitated as considerable time had elapsed since last revision in 1971 during which structural changes in the State’s economy might have taken place. The choice of appropriate base year for this purpose was considered by the Advisory Committee on National Income and also by the Working Group on State Income constituted by the Central) Statistical Organisation, Government of India.
Economic and Statistical Organisation, Planning Department, Government of Haryana